Pretend play and language development among preschool children: a meta-analysis - Kim, Soomin (Kansas State University, 2018)
Language development in early childhood is an important indicator and precursor for children’s later development in various areas, such as emotional, social, cognitive, and academic development. Studies have shown that pretend play, as one of the predominant play types during the preschool period, is an important activity to facilitate children’s learning experiences and exploration. However, there has been a lack of consistency in findings across studies due to different study designs. It is likely that these varying study characteristics have resulted in the variability of effects in the pretend play-language relationship, which has been also suggested by previous reviews. These factors point to the potential of meta-analysis for organizing the studies into a common paradigm and better understanding the practical significance of play-language relationships. The current meta-analysis systematically reviewed and analytically investigated 25 existing empirical studies that had examined the associations between pretend play and language development among young children. The overall magnitude of the association between pretend play and language development, .36, showed a moderate association. Furthermore, moderator analyses indicated that several factors, such as the role of adults or children’s play types, tended to have considerable impacts on the associations between pretend play and language development. This study has determined the strength of the research foundation that currently supports inclusion of pretend play in preschool classrooms and has charted future research on the pretend play-language associations in the early childhood research field.
Keywords: Meta-analysis; Pretend play; Language development